Lumbopelvic Muscle Mechanical Properties in Women with Multiple Sclerosis: A Cross-Sectional Case-Controlled Study - Inés Cruz-Medel; María Ángeles Peña-Toledo; Francisco Alburquerque-Sendín; Daiana Priscila Rodrigues-de-Souza; Cristina Conde-Gavilán; Ana María Jover-Sánchez; Claudia Carmona-Medialdea; Eduardo Agüera-Morales (Biomedicines)
Background/Objectives: To compare the lumbopelvic muscle mechanical properties (MMPs) of women with and without multiple sclerosis (MS) and explore relationships between these properties and sociodemographic/clinical characteristics. Methods: This cross-sectional observational study included 22 women with MS and 22 age- and BMI-matched women without MS. MMPs (frequency, stiffness, decrement, relaxation, and creep) of pelvic floor and lumbar paravertebral muscles were assessed using a MyotonPRO device. Sociodemographic and clinical data related to pelvic floor health were also collected. Results: Women with MS showed significant differences in pelvic floor MMPs, including higher frequency (3.26 Hz; 95% CI [2.12, 4.41]), stiffness (90 N/m; 95% CI [55.09, 124.91]), and decrement (0.2; 95% CI [0.09, 0.31]), and lower relaxation (6.15 ms; 95% CI [8.26, 4.05]) and creep (0.24; 95% CI [0.34, 0.13]) compared to women without MS. For lumbar paravertebral muscles, differences were observed only on the right side, with lower frequency (2.15 Hz; 95% CI [0.28, 4.02]) and stiffness (62.17 N/m; 95% CI [10.7, 113.65]) in women with MS. Correlation patterns between MMPs and clinical characteristics differed by group, with moderate correlations found only in the MS group (e.g., EDSS: r = 0.57; p = 0.006; PFDI-20: r = 0.47; p = 0.026). Conclusions: Women with MS exhibit altered pelvic floor MMPs, characterized by reduced tone and stiffness and increased elasticity and viscoelasticity, while lumbar paravertebral differences are minimal. These findings highlight the need for objective MMP assessments in women with MS to guide preventive and therapeutic interventions.